Job creation and trade in manufactures: Industry-level analysis across countries - Admasu Shiferaw; Degol Hailu (IZA Journal of Labor & Development, 2016)
This paper examines industry-level responses of manufacturing employment in the context of globalization using a large sample of developed, developing, and transition economies. We find that developing countries need atypically high rates of value-added growth (about 10 %) to increase manufacturing employment appreciably (about 4 %). The employment benefits of export orientation are also modest even in "comparative advantage" industries of developing countries. However, diversifying the export basket contributes significantly to employment growth, particularly in the medium- and high-technology industries. Import competition does not undermine employment growth in low-technology industries of developing countries while it displaces jobs in the same industries in Organisation for Economic Co-operation and Development (OECD) and transition economies. For developing countries, import-induced job losses are higher in the more capitalintensive medium-technology industries. Jobs in high-technology industries are less sensitive to imports with positive relationships observed in the OECD. Investment also complements job creation in low-technology industries of developing countries that have yet to industrialize.
Keywords: J21; L60; O14; O25; 330; Labor demand; Employment elasticity; Manufacturing; Export orientation; Import competition